2023
DOI: 10.1002/2211-5463.13596
|View full text |Cite
|
Sign up to set email alerts
|

Reversine attenuates cholestatic ductular reaction in rats

Abstract: Ductular reaction (DR) is usually observed in biliary disorders or various liver disorders, including nonalcoholic fatty liver disease. Few studies have focused on interrupting the DR process in the cholestatic environment. Here, we investigated the impact of reversine on DR in rats that had undergone bile duct ligation (BDL). Cholestatic injury was induced in rats 2 weeks following BDL. DR was assessed with biliary markers by immunohistochemistry. Biliary epithelial cells (BECs) were isolated for the analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…Although only two non‐hepatocarcinogens were tested in this study, cholestatic injury induced by bile duct ligation has been reported to cause expansion of EpCAM‐positive biliary epithelial cells, whereas no hepatocellular expression of EpCAM was observed in rats. 11 Similarly, in the CCl 4 /2‐AAF model of liver fibrosis, EpCAM was expressed in hepatic progenitor cells, reactive cholangiocytes located in the fibrous septa, and occasionally in scattered cells within the hepatic lobules but not in the majority of hepatocytes. 12 In contrast, although expression of APN in the rat liver after exposure to non‐hepatocacinogens has not been well studied, APN promoted sorafenib resistance through activation of the HDAC5‐LSD1‐NF‐κB signaling pathway, 13 and the suppression of APN enhanced the cytotoxic effect of chemotherapeutic reagents in hepatocellular carcinoma cells.…”
Section: Resultsmentioning
confidence: 93%
“…Although only two non‐hepatocarcinogens were tested in this study, cholestatic injury induced by bile duct ligation has been reported to cause expansion of EpCAM‐positive biliary epithelial cells, whereas no hepatocellular expression of EpCAM was observed in rats. 11 Similarly, in the CCl 4 /2‐AAF model of liver fibrosis, EpCAM was expressed in hepatic progenitor cells, reactive cholangiocytes located in the fibrous septa, and occasionally in scattered cells within the hepatic lobules but not in the majority of hepatocytes. 12 In contrast, although expression of APN in the rat liver after exposure to non‐hepatocacinogens has not been well studied, APN promoted sorafenib resistance through activation of the HDAC5‐LSD1‐NF‐κB signaling pathway, 13 and the suppression of APN enhanced the cytotoxic effect of chemotherapeutic reagents in hepatocellular carcinoma cells.…”
Section: Resultsmentioning
confidence: 93%